Rates and pathways of sedimentary organic matter mineralization in two basins of a boreal lake: Emphasis on methanogenesis and methanotrophy. (8th July 2016) - Clayer, François; Gobeil, Charles; Tessier, André
Abstract: Sediment porewater was analyzed at several sampling dates in two adjacent basins of an oligotrophic boreal lake, one basin perennially oxygenated (Basin A) and the other occasionally anoxic (Basin B). Depth concentration profiles of methane (CH4 ), dissolved inorganic carbon (DIC), and electron acceptors were modeled with a one‐dimensional transport‐reaction equation to constrain the depth intervals (zones) where solutes are produced/consumed in the top 10 cm of the sediment column, and to obtain the net reaction rates in each zone. This multicomponent geochemical modeling reveals that CH4 was produced below 4–7 cm depth at lower rates in Basin A (250–800 fmol cm −2 s −1 ) than in Basin B (1900–6500 fmol cm −2 s −1 ) and that methanogenesis accounted for 30–64% and 84–100% of the sediment organic matter (OM) mineralization in Basins A and B, respectively. We show that methanogenesis did not always yield equimolar amount of CH4 and DIC, as would be expected from the fermentation of the model molecule CH2 O. While ∼50% of the CH4 produced in Basin A is oxidized in the sediment column, this proportion decreases to ∼20% in Basin B. Dioxygen is by far the main electron acceptor for CH4 and OM oxidations in both basins. Methanotrophy in the sediment, however, is not limited to the ∼4‐mm thick surface layer in which O2 diffuses from bottom water but occurs down to 4–7 cm depth where O2 is transported through bioirrigation. Thermodynamic calculations suggest that, in addition to O2, Fe oxyhydroxides, and sulfate may serve as oxidants for methanotrophy in that zone. We predict that Basin B sediments release more CH4 than DIC whereas Basin A sediments mainly export DIC. This study highlights that small changes in hypolimnetic O2 levels may significantly alter the magnitude of OM mineralization pathways and the fate of CH4 in boreal lake sediments.